Monetary and macroprudential policies in an estimated model with financial intermediation - Paolo Gelain; Pelin Ilbas (National Bank of Belgium, 2014)
We estimate the Smets and Wouters (2007) model augmented with the Gertler and Karadi (2011) financial intermediation sector on US data by using real and financial observables. Given the framework of the estimated model, we address the question whether and how standard monetary policy should interact with macroprudential policy in order to safeguard real and financial stability. For this purpose, monetary policy is described by a flexible inflation targeting regime using the interest rate as instrument, while the macroprudential regulator adopts a tax/subsidy on bank capital in a countercyclical manner in order to stabilize nominal credit growth and the output gap. We look at the gains from coordination between the central bank and the macroprudential regulator under alternative assumptions regarding the degree of importance assigned to output gap fluctuations in the macroprudential mandate. The results suggest that there can be considerable gains from coordination if the macroprudential regulator has been assigned a sufficiently high weight on output gap stabilization, i.e. the common objective with monetary policy. If, on the other hand, the main focus of the macroprudential mandate is on credit growth, the macroprudential policy maker can reach better outcomes, while the central bank does worse, in the absence of coordination. Therefore, whether and to which extent monetary policy gains from coordination with the macroprudential regulator depends on the relative weight assigned to output fluctuations in the macroprudential mandate. Our counterfactual analysis further confirms the effectiveness of the countercyclical macroprudential tax/subsidy in containing the amplification effects triggered by a financial shock, and suggests that having a macroprudential regulatory tool at work could have successfully avoided the massive drop in credit such as the one observed at the onset of the Great Recession.
Keywords: E42; E44; E52; E58; E61; 330; Monetary policy; financial frictions; macroprudential policy; policy coordination; capital tax/subsidy; Geldpolitik; Finanzmarktaufsicht; Inflationssteuerung; Kapitalertragsteuer; Wirkungsanalyse; Schätzung; USA